2020
DOI: 10.7150/jca.46386
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics profile and prognostic gene signature of m6A regulators in uterine corpus endometrial carcinoma

Abstract: Uterine corpus endometrial carcinoma (UCEC) is the most common type of gynecologic malignancy worldwide. Despite advances in the treatments of UCEC, its incidence and mortality rates are still increasing. N6-methyladenosine (m6A) is the most common form of RNA modification and has attracted increasing interest in cancer pathogenesis and progression. Thus, we aimed to identify the landscape of m6A regulators and build a prognostic gene signature in UCEC. In this study, we first analyzed copy number variations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Uterine corpus endometrial carcinoma (UCEC) is a gynecological malignant disease with high mortality, 1 which came in fourth after breast cancer, rectum, and lung cancer. 2 The incidence rate and mortality of UCEC are continuing to rise.…”
Section: Introductionmentioning
confidence: 99%
“…Uterine corpus endometrial carcinoma (UCEC) is a gynecological malignant disease with high mortality, 1 which came in fourth after breast cancer, rectum, and lung cancer. 2 The incidence rate and mortality of UCEC are continuing to rise.…”
Section: Introductionmentioning
confidence: 99%
“…Then, all patients were into a high or low-risk group according to the median value as a cutoff to separately dichotomize the training sets in LUAD and LUSC, and a low-risk score indicates a superior prognosis for patients. This similar approach has been identified from previous studies [21,22]. Finally, the risk-score signature of prognosis was verified in the testing sets, which integrated from the GEO cohorts (GSE30219, GSE31210, GSE3141, GSE37745, GSE50081, GSE68465).…”
Section: Risk-score Model Constructionmentioning
confidence: 73%
“…Univariate Cox regression analysis showed that IGF2BP1, KIAA1429, IGF2BP3, YTHDF3, and IGF2BP2 were closely related to the survival and prognosis of endometrial cancer patients. Among them, IGF2BP3, KIAA1429, and IGF2BP1 can effectively predict the prognosis of patients (93). In addition, Pang et al found that IGF2BP1 and YTHDF3 had a strong ability to stratify the prognosis of different endometrial cancer patients (94).…”
Section: Prognostic Effect Of M 6 a Rna Methylation Regulators On End...mentioning
confidence: 99%